Analisis Persepsi Guru Terhadap Efektivitas Pembelajaran Biologi Berbasis Technological Knowledge di SMA Kecamatan Samarinda Ulu - Pradana, Nirza; Masitah; Nasution, Ruqoyyah; Serena, Nelda Anasthasia (PendIPA Journal of Science Education, 2025)
The development of technology in the education sector today is not accompanied by wise use by students. One way to increase the productivity of technology use by students is through schools, where teachers act as facilitators. This certainly poses a challenge for teachers to maximize the role of technology in schools despite differences and limitations so that learning becomes effective. Teachers' perceptions of technology are important to analyze in efforts to improve the quality of technology-based learning. This study aims to determine teachers' perceptions of the effectiveness of biology learning based on technological knowledge at Samarinda Ulu District High School and the factors influencing it. The methods used are qualitative and quantitative, with measurement tools in the form of questionnaires and interview sheets. Data were analyzed using descriptive statistical analysis. Based on the questionnaire responses from 7 biology teachers at SMA Kecamatan Samarinda Ulu, the analysis of teachers' perceptions of the effectiveness of technology-based biology learning revealed a score of 71.42%, indicating that the majority of teachers have a very positive perception of the effectiveness of technology-based learning. Factors influencing this include teachers' and students' ability to use technology, the availability of infrastructure, the suitability of technology to the material presented, the diversity of applications used in learning, and discipline and motivation in learning.